Narrative review on endovascular techniques for left subclavian artery revascularization during thoracic endovascular aortic repair and risk factors for postoperative stroke. (12th February 2021) - D'Oria, Mario; Mani, Kevin; DeMartino, Randall; Czerny, Martin; Donas, Konstantinos P; Wanhainen, Anders; Lepidi, Sandro
Abstract:  : OBJECTIVES: The aim of this study was to present a narrative review on endovascular techniques (ET) for revascularization of the left subclavian artery (LSA) during zone 2 thoracic endovascular aortic repair (TEVAR) and on risk factors for postoperative stroke following TEVAR procedures. METHODS: Non-systematic search of the literature from the PubMed, Ovid and Scopus databases to identify relevant English-language articles fully published in the period 1 January 2010–1 August 2020. RESULTS: Current general agreement is that LSA revascularization should be always attempted in the elective setting. Under urgent circumstances, it can be delayed but might be considered during the same session on a case-by-case basis. Three ET are currently available: (i) chimney/snorkels (also known as parallel grafts), (ii) fenestrations or branches and (iii) proximal scallops. The main issue with ET is the potential for increased peri-operative stroke risk owing to increased manipulation within the aortic arch. Also, they are relatively novel and further assessment of their long-term durability is needed. Intra-operative embolism and loss of left vertebral artery perfusion are hypothesized as the main causes of stroke in patients undergoing TEVAR. CONCLUSIONS: The overall risk of stroke seems higher without LSA revascularization during zone 2 TEVAR. As LSA revascularization might have a direct effect in preventing posterior stroke, it should be routinely performed in elective cases, while a case-by-case evaluation can be made under urgent circumstances. While ET can provide effective options for LSA revascularization during zone 2 TEVAR, they are novel and need further durability assessment. Stroke after TEVAR is a multifactorial pathological process and preventing TEVAR-related cerebral injury remains a significant unmet clinical need.